Anti-glioblastoma Activity of Kaempferol via Programmed Cell Death Induction: Involvement of Autophagy and Pyroptosis - Chen, Suqin; Ma, Jing; Yang, Liu; Teng, Muzhou; Lai, Zheng-Quan; Chen, Xiaoyu; He, Jingjin (Frontiers in Bioengineering and Biotechnology, 2020)
Glioblastoma is one of the most common and lethal intracranial malignant, and it is still lack of ideal treatments. Kaempferol is a major nutrient found in various edible plants, which has exhibited the potential for the treatment of glioblastoma. However, the specific anti-glioma mechanism of kaempferol is yet to be studied. Herein, we aim to explore the mechanisms underlying the anti-glioma activity of kaempferol. Our results demonstrated that kaempferol suppresses glioma cell proliferation in vitro and inhibits tumor growth in vivo. Moreover, kaempferol raises ROS and decreases mitochondrial membrane potential in glioma cells. The high levels of ROS induce autophagy then ultimately trigger the pyroptosis of glioma cells. Interestingly, when we used 3-MA to inhibit autophagy, we found that the cleaved form of GSDME was also decreased, suggesting that kaempferol induces pyroptosis through regulating autophagy in glioma cells. In conclusion, this study revealed kaempferol possesses good anti-glioma activity by inducing ROS, and subsequently leads to autophagy and pyroptosis, highlighting its clinical potentials as a natural nutrient against glioblastoma.